Diabetic peripheral neuropathy - advances in diagnosis and treatment - Bigos, Paula; Dendys, Konrad; Bieniasz, Jan; Kuźnicki, Wojciech; Matkowski, Igor; Potyrała, Piotr (Journal of Education, Health and Sport, 2023)
Diabetes mellitus is one of the most alarming conditions of the 21st century. The prevalence of both type 1 and 2 diabetes is constantly increasing, which also entails a growing number of patients suffering from its various complications. One of the most common chronic complications is diabetic neuropathy (DN), which is developed by at least 50% of patients with diabetes. Diabetic peripheral neuropathy (DPN) is the most frequent type of DN. Clinically, a non-painful and a painful-DPN can be distinguished. The painful type causes a massive decrease in the quality of life and affects around 30% of individuals with DM. In recent years many instruments have been used to diagnose and treat DPN but none of them seems to be sufficient in early diagnosis and satisfactory symptoms management. To date, there is any gold standard to recognize DNP and usually it is noticed when a patient presents symptoms of neuropathy, which is too late to introduce an effective therapy. The main approaches for patients with DNP focus on improving glycaemic control, lifestyle modifications and pain therapy. Multiple medicaments are used for this purpose, among which SNRIs, TCAs and anticonvulsants are most effective. Non-pharmacologic treatment, such as acupuncture, physical therapy, nerve stimulation, also has been used, however their effectiveness remains uncertain.